How the organisation of medical work shapes the everyday work experiences underpinning doctor migration trends: The case of Irish-trained emigrant doctors in Australia. Issue 4 (April 2021) - Byrne, John-Paul; Conway, Edel; McDermott, Aoife M.; Matthews, Anne; Prihodova, Lucia; Costello, Richard W.; Humphries, Niamh
Highlights: Hospital doctors' working conditions and emigration rates are intricately interconnected. Participants described contrasting experiences working in Irish and Australian health systems. Contrasting experiences were shaped by the organisational features of medical work. Effective retention requires an understanding of how health systems shape frontline experiences. Abstract: Medical migration is a global phenomenon. In Ireland, hospital doctor emigration has increased significantly in recent years, with Australia a destination of choice. With work and employment conditions cited as a driver of these trends, this article explores how health system differences in the organisation of medical work shape the everyday experiences of hospital doctors which underpin migration decisions. Drawing on 51 semi-structured interviews conducted in July-August 2018 with Irish-trained hospital doctors who had emigrated to work in Australia, the findings highlight doctors' contrasting experiences of medical work in the Irish and Australian health systems. Key system differences in the organisation of medical work manifested at hospital level and related to medical hierarchy; staffing, support and supervision; and governance and task coordination. Findings indicate that retention of hospital doctors is as much about the quality of the work experience, as it is about the quantity and composition of the workforce. At a time of international competition for medical staff, effective policy for the retention of hospital doctors requires an understanding of the organisation of work within health systems. Crucially, this can create working contexts in which doctors flourish or from which they seek an escape.